2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC) 2015
DOI: 10.1109/pvsc.2015.7356416
|View full text |Cite
|
Sign up to set email alerts
|

Bifacial Cu(In,Ga)Se2 solar cells with submicron absorber thickness: back-contact passivation and light management

Abstract: For bifacial Cu(In,Ga)Se 2 solar cells with submicron absorber thickness, an Al 2 O 3 -layer deposited by a simple, self-organized spray-pyrolysis process onto the transparent SnO 2 :F back-contact is used to increase open circuit voltage and thereby increase power conversion efficiency, especially for rear-illumination, indicating reduced charge carrier back-contact recombination. On non-passivated SnO 2 :F, a thin (10nm) Mo-layer improved the electrical back-contact properties, while on Al 2 O 3 -passivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…In the past, this has been achieved by a selective removal of Al 2 O 3 covered CdS particles, a dispersion of Mo nanoparticles, and by electron beam‐ or photo‐ lithography. Ohm et al applied a 2‐step process, based on spray pyrolysis and selective etching, to deposit a porous Al 2 O 3 layer on FTO and could prove a beneficial passivation effect for the TBC/CIGS interface . The deposition of thick Al 2 O 3 (with openings) probably reduces the impact of the IOH thickness, because a significantly reduced Na supply from the glass is expected.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, this has been achieved by a selective removal of Al 2 O 3 covered CdS particles, a dispersion of Mo nanoparticles, and by electron beam‐ or photo‐ lithography. Ohm et al applied a 2‐step process, based on spray pyrolysis and selective etching, to deposit a porous Al 2 O 3 layer on FTO and could prove a beneficial passivation effect for the TBC/CIGS interface . The deposition of thick Al 2 O 3 (with openings) probably reduces the impact of the IOH thickness, because a significantly reduced Na supply from the glass is expected.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…A supposedly detrimental Ga 2 O 3 formation at the absorber/TCO interface (for AZO and ITO) or a reduced conductivity of FTO by a fluorine loss during high temperature absorber deposition was suggested as possible origin. On the other hand, Mollica et al have demonstrated ohmic behavior of FTO and AZO layers on CIGS (deposited at T CIGS > 500°C) and used these materials as appropriate TBCs in ultra‐thin CIGS devices . Thus, the applicability of the TCO films as a TBC seems to depend on details in the absorber processing like the incorporation of alkaline atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the effects and influence of back surface passivation in CIGS solar cells, there are studies that used bi-facial thin CIGS solar cells [28][29][30]. For bi-facial solar cells, all characterizations are made from both the front and back side of the solar cell.…”
Section: Approaches Used To Add the Passivation Layermentioning
confidence: 99%
“…Still, the light-trapping efficiency of these devices is limited by the low reflectivity of the Mo back contact. The choice of alternatice materials (ZrN 65 ,TCO 66,67,68 ) is constrained by the high temperature of the CIGS deposition process. For this reason, highly reflective metals like Au 69 and Ag 70 have only been introduced in a superstrate configuration.…”
Section: Box 1: Light-trapping In Solar Cellsmentioning
confidence: 99%
“…CIGS is usually grown by co-evaporation, sputtering or electrodeposition on Mo, a refractory material that forms an ohmic contact with the CIGS thanks to the creation of a thin MoSe 2 interface layer. Alternative back contact materials with higher optical reflectance and lower surface recombination are currently under investigation in several groups 66,67,70 . Silver mirrors encapsulated with transparent conducting oxides appear as a promising candidate 68 .…”
Section: Fabricating Ultrathin Absorber Layersmentioning
confidence: 99%